Teaching science - Levinson, Ralph, 1951- (Open University Postgraduate Certificate in Education (Series), 1994)
Science education has undergone far-reaching changes in the last fifty years. The articles collected together in this reader examine how we have reached our present consensus and what theories we now use to explain how children learn science. The central sections of the reader examine how all this can be translated into effective and stimulating teaching, how learning can be most accurately and fairly assessed and how the impact of gender, ethnicity and other factors on children's performance can be addressed in methods of teaching which make science accessible to all. The articles in the fina.